In vivo and In vitro studies of Bacillus megaterium var. phosphaticum on nutrient mobilization, antagonism and plant growth promoting traits - Amalraj, E. Leo Daniel; Maiyappan, S; Peter, A John (Journal of Ecobiotechnology, 2012)
Nutrient solubilisation efficiency, plant growth promoting traits and antagonistic effects of Bacillus megaterium var. phosphaticum were studied in the laboratory and screen house during 2010-11 at Hyderabad, India. Plate agar assay indicated varied solubilisation level when the media was blended with zinc carbonate (35.6%), zinc oxide (31.1%), k-bentonite (23%), rock phosphate (19.8%), tricalcium phosphate (3.1%) and zinc sulphide (0.0%). The release of available zinc is high (17.4 ppm) on day-12 when the test organism was grown in liquid media blended with zinc carbonate. The media pH was inversely proportional to the amount of nutrients solubilised on day-12. B. megaterium var. phosphaticum is found to produce plant growth promoting substances like biofilm and chitinase enzymes (strong), giberrellic acids and siderophores (moderate) and indole acetic acid (weak). Confrontation assay confirmed it’s strong antagonistic activity against Rhizoctonia solani (41%), Macrophomina phaseolina (42%), Sclerotium rolfsii (27%) and Fusarium oxysporum (40%). The production of siderophores and chitinase enzymes justifies the strong antagonistic activity against these fungal pathogens. Potted plant assay using sunflower, Helianthus annuus as the test crop indicated superior plant growth and photosynthetic activities in treatment with B. megaterium var. phosphaticum + 75% of recommended chemical fertilizer dose as compared to treatment with 100% chemical fertilizers. It also improved significantly the uptake of nitrogen (7.97mg/100g dry mass), phosphate (3.41mg/100g dry mass), potash (38.12mg/100g dry mass), zinc (184mg/100g dry mass), iron (743mg/100g dry mass) and manganese (138mg/100g dry mass) as compared to treatments with 100% B. megaterium var. phosphaticum, 100% chemical fertilizers and untreated control. The findings of current study suggest reduction of 25% recommended dose of chemical fertilizers in combination with B. megaterium var. phosphaticum as seed dresser and soil application.